2022
DOI: 10.1002/smll.202107557
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Triggered Metallic 1T’ Phase Transformations of Chemically Exfoliated Tungsten Disulfide (WS2) Nanosheets

Abstract: Developing facile methods for inducing phase transformation between metallic and semiconducting 2D transition metal dichalcogenide (TMDC) materials is crucial toward leveraging their use in cutting‐edge energy devices. Herein, 2H‐to‐1T’ phase transformations in chemically exfoliated Tungsten Disulfide (WS2) nanosheet films, triggered by antioxidants toward highly conductive 2D TMDC electrode materials, are introduced. It is found that antioxidants cause residual LiOx compounds to reduce to Li metal, subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…WO 3 is fully sulfided with sufficient S source, and excess NH 4+ ions intercalate between the S-W-S interlayer to generate 1T-WS 2 nanosheets. 8 However, the diffraction peak of WS 2(8:1) -240 °C was not found at 9.3°, which may be due to a phase transition by the interaction of cations with S. 53 Although the content of WS 15 The result indicated that the sample was pure WO 3 nanorods. In WS x O y(5:1) -180 °C, there were two new feature peaks located at 352 cm −1 and 418 cm −1 , reflecting the inplane E 1 2g and out-of-plane A 1g vibration peaks of WS 2 , respectively.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…WO 3 is fully sulfided with sufficient S source, and excess NH 4+ ions intercalate between the S-W-S interlayer to generate 1T-WS 2 nanosheets. 8 However, the diffraction peak of WS 2(8:1) -240 °C was not found at 9.3°, which may be due to a phase transition by the interaction of cations with S. 53 Although the content of WS 15 The result indicated that the sample was pure WO 3 nanorods. In WS x O y(5:1) -180 °C, there were two new feature peaks located at 352 cm −1 and 418 cm −1 , reflecting the inplane E 1 2g and out-of-plane A 1g vibration peaks of WS 2 , respectively.…”
Section: Resultsmentioning
confidence: 93%
“…WO 3 is fully sulfided with sufficient S source, and excess NH 4+ ions intercalate between the S–W–S interlayer to generate 1T-WS 2 nanosheets. 8 However, the diffraction peak of WS 2(8:1) -240 °C was not found at 9.3°, which may be due to a phase transition by the interaction of cations with S. 53 Although the content of WS 2 spans directly from 0% to 100% as the S source increases, the process of vulcanization still occurred. The formation process of WS 2(10:1) -240 °C nanoflowers is described in detail (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Photothermal therapy (PTT) is an innovative antibacterial strategy that utilizes photothermal agents (PTAs) to convert laser energy into thermal energy . PTT can disrupt bacterial membranes, denature proteins, and lead to irreversible bacterial destruction. , PTT offers several advantages over traditional antibiotic therapy, including broad-spectrum antibacterial activity, remote controllability, targeting selectivity, rapid effectiveness, and less side effects. , Various materials with photothermal properties, such as noble-metal-based nanomaterials, carbon-based nanomaterials, semiconducting polymers, and photosensitive organic dyes, have been explored for PTT applications. Noteworthily, some PTAs have limited photothermal capacity, high cost, and potential cytotoxicity . Therefore, the choice of PTAs could be essential for antibacterial and wound healing efficiency and biosafety.…”
Section: Introductionmentioning
confidence: 99%
“…The metastable 2M-phase WS 2 with metallic nature exhibits enhanced catalytic activity, ,,, which is a promising TMD-based electrocatalyst for HER. However, it is metastable and is easily transformed into the thermodynamically more stable 2H phase with poor activity. To address these issues, several effective strategies have been implemented to improve its stability, such as surface adsorption of functional groups and cation insertion for electronic regulation. , However, these strategies cannot solve the phase degradation issue intrinsically, especially after exfoliation with an enhanced specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…32,36−39 The Jahn−Teller distortion of octahedral coordination in 1T-phase WS 2 will further cause the phase transition to form a triangular cluster stacking 1T″′ structure and a zigzag chain-like 1T′ structure (2M phase). 40−43 The metastable 2M-phase WS 2 with metallic nature exhibits enhanced catalytic activity, 40,42,44,45 which is a promising TMD-based electrocatalyst for HER. However, it is metastable and is easily transformed into the thermodynamically more stable 2H phase with poor activity.…”
Section: Introductionmentioning
confidence: 99%